1982
DOI: 10.1094/pd-66-336
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Cowpea Mild Mottle Virus from Diseased Soybeans in the Ivory Coast

Abstract: A virus isolated from soybeans showing severe mosaic was identified as an isolate of cowpea mild mottle virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 1 publication
0
19
0
1
Order By: Relevance
“…Brunt and Kenten (1973) reported a seed transmission level of 92% (33 out of 36 seeds) in soybean. Iwaki et al (1982), however, found 0.9~ seed transmission in soybean (one out of 110 seeds) and Thouvenel et al (1982) found 0.5070 (one out of 200 seeds) and 8.3~ (five out of sixty seeds) for two soybean cultivars. Iizuka et al (1984) grew out 500 soybean seeds from CMMV-infected plants, but none of the seedlings showed typical disease symptoms.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Brunt and Kenten (1973) reported a seed transmission level of 92% (33 out of 36 seeds) in soybean. Iwaki et al (1982), however, found 0.9~ seed transmission in soybean (one out of 110 seeds) and Thouvenel et al (1982) found 0.5070 (one out of 200 seeds) and 8.3~ (five out of sixty seeds) for two soybean cultivars. Iizuka et al (1984) grew out 500 soybean seeds from CMMV-infected plants, but none of the seedlings showed typical disease symptoms.…”
mentioning
confidence: 88%
“…However, these results together with those of the extensive study done at IITA (IITA, 1987) and the test conducted by Iizuka et al (1984) show that the general view that CMMV is seed transmitted should be reconsidered. Brunt and Kenten (1973), Iwaki et al (1982) and Thouvenel et al (1982) found seed transmission of CMMV, using other strains and other cultivars. In these studies only growing-out tests were applied, but no special precautions were reported to prevent accidental contamination with CMMV.…”
mentioning
confidence: 93%
“…Cowpea mild mottle virus (CPMMV; family Betaflexiviridae, genus Carlavirus) is a serious problem in Brazilian soybean (Glycine max), causing dwarfing, chlorosis, vein clearing/mosaic, leaf and stem necrosis (Iwaki et al, 1982;Almeida et al, 2003;Almeida, 2008;Tavasoli et al, 2009). The virus was originally reported infecting cowpea (Vigna unguiculata) in Ghana (Brunt & Kenten, 1973;Tavasoli et al, 2009) and was subsequently found causing mosaic and leaf crinkling in soybean in Thailand (Iwaki et al, 1982) and the Ivory Coast (Thouvenel et al, 1982). At around the same time, it was reported in Brazil in common bean (Phaseolus vulgaris) cv.…”
Section: Introductionmentioning
confidence: 98%
“…CPMMV was first reported on cowpea in Ghana [1], and subsequently reported from several tropical regions of Africa [2,3,4,5,6], Asia [7,8,9,10], Brazil and Argentina [19,20], as well as from the Ivory Coast [21]. …”
Section: Resultsmentioning
confidence: 99%
“…Since then, it has been subsequently reported from several tropical regions of Africa [2,3,4,5,6], Asia [7,8,9,10], Brazil and Argentina [1,11], and from the Ivory Coast [12]. The experimental host range of CPMMV includes plant species from several families, which mainly display chlorotic local lesions or systemic mottle upon inoculation or infection.…”
Section: Introductionmentioning
confidence: 99%